Rebound of superficial hemangioma after suspension of topical propranolol. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Early administration of topical 1% propranolol in superficial hemangioma is often effective in blocking growth and leads to improvement in about 80% of cases (2). However, as for oral treatment the most important side effect of topical therapy is the rebound of hemangioma when topical propranolol is withdrawn. The rebound phenomenon was more common in the past when the hemangioma therapy with beta-blockers was continued for 4-5 months similarly to what was usually done in pre-beta-blocker therapy with corticosteroids. When beta-blocker treatment was prolonged up to the year of life or at least 7 months the rebound incidence decreased significantly. The current case confirms the need to continue topical therapy with beta-blockers throughout the growth period of hemangioma, which is very variable from case to case.